104k views
5 votes
Which expressions are equivalent to 3(6+b)-(2b + 1)?

Select two answers.
Step 1 - Use the distributive property and pick your first answer
Step 2 - Combine like terms and pick your second answer.

User Daltron
by
6.8k points

1 Answer

6 votes

Answer:

18+3b-2b-1

b+17

Explanation:


\mathrm{Using\:the\:distributive\:law}:\quad \:-\left(a+b\right)=-a-b


-\left(2b+1\right)=-2b-1


=3\left(6+b\right)-2b-1


=18+3b-2b-1


\mathrm{Group\:like\:terms}


=3b-2b+18-1


\mathrm{Subtract\:the\:numbers:}\:18-1=17


=3b-2b+17


\mathrm{Add\:similar\:terms:}\:3b-2b=b


=b+17

[RevyBreeze]

User Mo Zaatar
by
7.6k points